2014
DOI: 10.1039/c4nj01183j
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of oriented attachment in the growth of functionalized ZnTe nanoparticles for potential applications in bio-imaging

Abstract: This study reports a solution based, low temperature route towards the synthesis of water soluble cysteine capped zinc telluride (ZnTe) nanoparticles under the influence of variations in pH and reaction time. The optical properties of the ZnTe nanoparticles display broad emission peaks ranging between 365-415 nm, which make them useful for imaging and biological labelling applications. Transmission electron microscopy (TEM) and high resolution TEM studies indicated that the particles are uniform in size and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Previous reports on ZnTe nanoparticles show emission in the 400-600 nm range depending on its size, shape and surface modications. [38][39][40][41][42][44][45][46] In the case of materials where the gold core is surrounded by a semiconductor shell the emission from the shell material is quenched due to electron transfer to the metal core. 47 It is therefore conceivable that the emission in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on ZnTe nanoparticles show emission in the 400-600 nm range depending on its size, shape and surface modications. [38][39][40][41][42][44][45][46] In the case of materials where the gold core is surrounded by a semiconductor shell the emission from the shell material is quenched due to electron transfer to the metal core. 47 It is therefore conceivable that the emission in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that ZnTe nanoparticles displayed uorescence properties that are useful in bioapplications. 42 The presence of cysteine has the potential to support conjugation of biomolecules and chemotherapeutic drugs which may enable this system to be applied in targeted drug delivery and bio-imaging applications within the domain of oncology therapeutics and diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…The results from Near infra‐red (NIR) induced photothermal conversion, NIR induced photodynamic property, cytocompatibility of Cu 2 Te nanocubes, doxorubicin (DOX) loading and release, In vitro cellular imaging and chemo‐toxicity of NCs‐DOX conjugate, NIR induced cellular photothermal ablation, NIR induced cellular photodynamic therapy, synergistic combinatorial therapy demonstrate that combinational therapy can be a wonderful technique for development of analytical therapeutic approaches for hypermethylated breast cancers. Cysteine stabilized ZnTe nanoparticles were synthesized by Dunpal et al . at different pH values.…”
Section: Synthetic Methods For Metal Telluride Nanomaterialsmentioning
confidence: 99%
“…The synthesis of the CdTe was carried out using methods described previously [17,[38][39][40] but with some slight modifications [41][42][43]. All reactions were carried out under an inert atmosphere using nitrogen gas.…”
Section: Synthesis and Characterization Of Cdte-qdsmentioning
confidence: 99%